Assessment of Reticulocyte and Erythrocyte Parameters From Automated Blood Counts in Vaso-Occlusive Crisis on Sickle Cell Disease - Feugray, Guillaume; Kasonga, Fiston; Grall, Maximilien; Benhamou, Ygal; Bobée-Schneider, Victor; Buchonnet, Gérard; Daliphard, Sylvie; Le Cam Duchez, Véronique; Lahary, Agnès; Billoir, Paul (Frontiers in Medicine, 2022)
Sickle cell disease is a complex genetic disease involving cell adhesion between red blood cells, white blood cells, platelets and endothelial cells, inducing painful vaso-occlusive crisis (VOC). We assessed reticulocyte and erythrocyte parameters in a cohort of confirmed SCD patients, and investigated whether a combination of these routine laboratory biomarkers of haemolysis could be used to predict VOC development. Reticulocyte and erythrocyte parameters were evaluated using the Sysmex XN-9000 analyser. A total of 98 patients with SCD were included, 72 in steady state and 26 in VOC. Among the 72 patients in steady state, 22 developed a VOC in the following year (median: 3 months [2-6]). The following parameters were increased in SCD patients with VOC development compared to SCD patients without VOC development in the following year: reticulocyte count (94.6 109/L [67.8-128] vs 48.4 109/L [24.9-87.5]), immature reticulocyte count (259 109/L [181-334] vs 152 109/L [129-208]) reticulocyte/immature reticulocyte fraction (IRF) ratio (6.63 109/(L*%) [4.67-9.56] vs 4.94 109/(L*%) [3.96-6.61]), and medium fluorescence reticulocytes (MFR) (19.9% [17.4-20.7] vs 17.1% [15.95-19.75]). The association of a reticulocyte count of >189.4 109/L and an MFR of >19.75% showed a sensitivity of 81.8% and a specificity of 88% to predict VOC development in the following year. Based on our findings, a combination of routine laboratory biomarkers, as reticulocyte count, immature reticulocyte count and fluorescent reticulocyte fraction at steady state, could be used to predict VOC development in SCD.